Virulence and Antimicrobial Resistance Pattern of Aeromonas spp. Colonizing European Pond Turtles Emys orbicularis and Their Natural Environment. First Study from Poland - Leszek Guz; Aneta Nowakiewicz; Krzysztof Puk; Przemysław Zięba; Sebastian Gnat; Łukasz Matuszewski (Animals, 2021)
The aim of the study was to isolate and identify species belonging to the Aeromonas genus and evaluate the antimicrobial resistance and virulence patterns of isolates colonizing European pond turtles (Emys orbicularis) from natural environment of Eastern Poland. In total, 74 turtles and 15 samples of water from their natural environment were examined. More than 40 strains were isolated and identified: A. bestiarum (n = 1), A. hydrophila (n = 13), A. allosaccharophila (n = 2), A. salmonicida (n = 3), and A. veronii (n = 23). The highest incidence of resistance was noted for ampicillin (100%) and sulfamethoxazole (62.0%), followed by erythromycin and colistin (both 40.5%). Moreover, eight strains were intermediately resistant to meropenem (19%). Most Aeromonas isolates were found to possess more than one virulence gene among fla, aer, hlyA, act, ela, alt, and ast. We showed that the population of free-living European pond turtles was highly colonized by Aeromonas spp. Such strains may be an infectious agent not only for the population of turtles but also for other species of animals inhabiting their natural environment. Moreover, the undesirable properties of water quality caused by the presence of drug-resistant aeromonads could have a negative impact on human health.